Sustainable tourists, generous consumers, lifestyle inspirers: the attitudes and expectations of Zadar’s local authorities vis-à-vis digital nomads - Aris Dougas Chavarria (Netcom)
The rise of the digital nomad has prompted heated debates, particularly given its rising relevance and projected growth. While a considerable body of academic research has delved into various aspects of this phenomenon, local authorities’ understanding and expectations regarding digital nomads remain understudied. This article aims to fill this research gap by drawing on ethnographic research, mainly consisting of eight open-ended interviews with local stakeholders and participant observation in digital nomad gatherings. The findings uncover the perceptions of Zadar’s policymakers about digital nomads as individuals who can financially contribute through spending, extend the tourist season by flocking in during the off-season, and disseminate knowledge. Among other relevant contributions, this paper suggests that digital nomads might rather be thought of as “short-term locals” instead of “long-term tourists” regarding their consumption patterns; argues that tourism stakeholders conceive digital nomads as off-season tourist boosters but not a main tourist target group; and hints at the fact that digital nomad knowledge transfer is unlikely to occur without the needed platforms. In doing so, this article constitutes a timely contribution to the academic literature since it interrogates the approach of local authorities to digital nomadism and unveils its specificities in Dalmatia, Croatia and Southeast Europe.